Spitting Seeds From the Cud: A Review of an Endozoochory Exclusive to Ruminants - Delibes, Miguel; Castañeda, Irene; Fedriani, Jose M. (Frontiers in Ecology and Evolution, 2019)
Given their strong masticatory system and the powerful microbial digestion inside their complex guts, mammalian ruminants have been frequently considered seed predators rather than seed dispersers. A number of studies, however, have observed that ruminants are able to transport many viable seeds long distances, either attached to the hair or hooves (i.e. epizoochory) or inside their body after ingesting them (i.e. endozoochory). However, very few studies have investigated a modality of endozoochory exclusive to ruminants: the spitting of usually large-sized seeds while chewing the cud. A systematic review of the published information about this type of endozoochory shows a marked scarcity of studies. Nonetheless, at least 48 plant species belonging to 21 families are dispersed by ruminants by this way. Most of these plants are shrubs and trees, have fleshy or dry fruits with large-sized seeds, and are seldom dispersed via defecation. Many cases have been observed in tropical areas, where more frugivorous ruminant species occur, but other records are from temperate and dry areas, covering thus all continents except Antarctica. Twenty one species of ruminants from 18 genera have been reported as endozoochore spitters. They involve domestic and wild species belonging to the families Tragulidae, Cervidae and Bovidae. This suggests that almost any ruminant species could potentially eat fruits and regurgitate large hard seeds during rumination. Likely, this seed dispersal mechanism has been neglected due to the difficulty of observing rumination behaviour and locating spat seeds. Further research on the potential of wild and domestic ruminant species as long-distance seed dispersers through spitting seeds from the cud appears particularly important given their increasing pervasiveness and abundance worldwide.